A Case Study: Implementation of Active Learning and Problem-Based Learning Pedagogies in Freshman Undergraduate Course - Prasad, Ch. Rajendra; Samala, Srinivas; Yalabaka, Srikanth (Journal of Engineering Education Transformations, 2025)
Globally, educational institutions have been forced to close and transition to online teaching due to the Covid-19 pandemic. From the last two and half years the student’s attention span drastically reduced due to online teaching. The traditional teaching and learning practices will not grab the student attention. Hence, a novel teaching pedagogy is needed to enhance student’s attention span and learning. To address this problem, this paper presented implementation of active learning and problem-based learning pedagogies in freshman under graduate course. The undergraduate freshman course is the smart system design. The course instruction methods are divided into two parts. In the first part, active learning methods such as flipped classroom, and Jigsaw are implemented. In the second part, problembased learning is implemented. The implementation of these pedagogies results shows that the student attention span is increased, the students can work in teams and problem-solving skills are improved. Finally, these pedagogies make the students ready for next-generation engineers.